Role of Galectins in the Liver Diseases: A Systematic Review and Meta-Analysis - An, Yang; Xu, Shixue; Liu, Yiting; Xu, Xiangbo; Philips, Cyriac Abby; Chen, Jiang; Méndez-Sánchez, Nahum; Guo, Xiaozhong; Qi, Xingshun (Frontiers in Medicine, 2021)
Background: Galectins, a family of β-galactoside binding proteins, are related to the development and progression of various human diseases, such as cancer, heart failure, and chronic kidney disease. However, its role in liver diseases is unclear. Methods: The PubMed, EMBASE, and Cochrane Library databases were searched. Hazard ratios (HRs), odds ratios (ORs), and mean differences (MDs) with 95% confidence intervals (CIs) were pooled to evaluate the association of galectins with the outcomes and risk of liver diseases by a random-effect model. Results: Thirty-three studies involving 43 cohorts and 4,168 patients with liver diseases were included. In patients with hepatocellular carcinoma (HCC), high expression of galectin-1 and -3 in tissues were significantly associated with worse overall survival (galectin-1: HR=1.94, 95%CI=1.61-2.34, P<0.001; galectin-3: HR=3.29, 95%CI=1.62-6.68, P<0.001) and positive vascular invasion (galectin-1: OR=1.74, 95%CI=1.18-2.58, P=0.005; galectin-3: OR=2.98, 95%CI=1.58-5.60, P=0.001); but high expression of galectin-4 and -9 in tissues were significantly associated with better overall survival (galectin-4: HR=0.53, 95%CI=0.36-0.79, P=0.002; galectin-9: HR=0.56, 95%CI=0.44-0.71, P<0.001) and negative vascular invasion (galectin-4: OR=0.36, 95%CI=0.19-0.72, P=0.003; galectin-9: OR=0.60, 95%CI=0.37-0.97, P=0.037). Serum galectin-3 level was significantly higher in HCC (MD=3.06, 95%CI=1.79-4.32, P<0.001), liver failure (MD=0.44, 95%CI=0.23-0.66, P<0.001), liver cirrhosis (MD=1.83, 95%CI=1.15-2.51, P<0.001), and chronic active hepatitis B (MD=18.95, 95%CI=10.91-27.00, P<0.001); serum galectin-9 level was significantly higher in HCC (MD=3.74, 95%CI=2.57-4.91, P<0.001) and autoimmune hepatitis (MD=8.80, 95%CI=7.61-9.99, P<0.001). Conclusion: High galectin-1 and -3 and low galectin-4 and -9 expression indicate worse outcomes of HCC patients. Serum galectin-3 and -9 levels are positively associated with the risk of chronic liver diseases.